2022
DOI: 10.3390/pharmaceutics14081542
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Materials as Elements of Modern Drug Delivery Systems for Anti-Inflammatory Agents: A Review of Recent Achievements

Abstract: Interest in the use of mesoporous materials as carriers of medicinal substances has been steadily increasing in the last two decades. Mesoporous carriers have application in the preparation of delivery systems for drugs from various therapeutic groups; however, their use as the carriers of anti-inflammatory agents is particularly marked. This review article, with about 170 references, summarizes the achievements in the application of mesoporous materials as the carriers of anti-inflammatory agents in recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 167 publications
0
4
0
Order By: Relevance
“…M41S are applied as delivery agents because they have tunable particle size and morphology, uniform and tunable pore size, high surface area and pore volume, facile surface functionalization, stable physicochemical properties, and thermal stability [108]. Moreover, some mesoporous silica materials are characterized by biodegradability and biocompatibility [109]. Cytometry assays revealed that synthesized silica has no cytotoxicity against human peripheral blood mononuclear cells.…”
Section: -Applications Of M41s Materialsmentioning
confidence: 99%
“…M41S are applied as delivery agents because they have tunable particle size and morphology, uniform and tunable pore size, high surface area and pore volume, facile surface functionalization, stable physicochemical properties, and thermal stability [108]. Moreover, some mesoporous silica materials are characterized by biodegradability and biocompatibility [109]. Cytometry assays revealed that synthesized silica has no cytotoxicity against human peripheral blood mononuclear cells.…”
Section: -Applications Of M41s Materialsmentioning
confidence: 99%
“…3 Treatment for central nervous system disease 3.1 Nanocarriers for nose-to-brain drug delivery Drug delivery systems deliver a certain dose to a target site in the body and maintain the drug concentration in that area at a dose appropriate for the duration of the treatment (Moritz and Geszke-Moritz, 2022). Nanocarriers are loaded with drugs to achieve this purpose and to deliver drugs to the brain efficiently, where they are selectively released to the target site via transport to specific cells and tissues, avoiding side effects caused by systemic exposure; nanocarriers also help drugs cross the BBB and provide neuroprotection (Figure 2) (Wen et al, 2021).…”
Section: Airway Hazardsmentioning
confidence: 99%
“…The discovery of silica nanoparticles helped to overcome the limitations of currently used nanomaterials, such as poor solubility and bioavailability. It provoked its use in porous glass and disordered silica gels for drug-delivery applications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%